Development of a simplified numerical method for structural response analysis to blast load - Li, Jun; Hao, Hong (Elsevier BV, 2011)
The response of structural concrete elements under extremely short duration dynamic loads is of great concern nowadays. The most prevailing method to this problem is based on SDOF simplification. It is well known that the SDOF model can reliably predict the overall structural component response if the response follows predominantly a predefined damage mode such as shear or flexural mode. However, it cannot reliably predict localized failure of structures. Moreover, reliable deflection shape and damage criterion, which are critical for developing the equivalent SDOF model, are difficult to define. Therefore, although most design and analysis are still based on SDOF approach, more and more analyses are conducted with detailed Finite Element (FE) modelling. However, due to the short time duration as well as the huge loading magnitude, it is extremely difficult and time consuming to perform FE structural response analysis to blast loads, even with modern computer power. In this paper, a numerical approach, which substantially reduces the modelling and computational effort in analysing structural responses to blast load, is presented. Based on the short duration of blast load, the structural response is divided into two parts: forced vibration phase and free vibration phase. In the proposed method, the response during the forced vibration phase is approximately solved using the SDOF approach. Using the estimated response quantities at the end of the forced vibration phase as the initial conditions, a detail FE model in LS-DYNA is established and free vibration response is solved. This approach, while yielding reasonably accurate response calculations, substantially reduces the modelling and computational effort. To demonstrate the method, a reinforced concrete beam is analysed using both the conventional detailed FE modelling and the proposed approach. Comparisons of the numerical results from the two methods demonstrate the reliability of the proposed method. Compared to the detailed FE modelling, the proposed method requires only a rather coarse FE mesh, and can use a larger integration time step for free vibration calculations. Therefore, it requires less than 5% of the computational time to predict the structural responses as compared to the detailed FE modelling approach.